Yield of epileptiform EEG abnormalities in incident unprovoked seizures: a population-based study - Baldin, Elisa (2014)
OBJECTIVE: The yield of epileptiform abnormalities in serial EEGs has not been addressed in a population-based setting for subjects with incident epilepsy or a single unprovoked seizure, raising the possibility of methodological limitations such as selection bias. Our aim was to address these limitations by assessing the yield and predictors of epileptiform abnormalities for the first and subsequent EEGs in a study of incident epilepsy or single unprovoked seizure in Rochester, Minnesota. METHODS: We used the resources of the Rochester Epidemiology Project to identify all 619 residents of Rochester, Minnesota born in 1920 or later with a diagnosis of incident epilepsy (N=478) or single unprovoked seizure (N=141) between 1960 and 1994, who had at least one EEG. Information on all EEGs and their results was obtained by comprehensive review of medical records. RESULTS: Among subjects with epilepsy, the cumulative yield of epileptiform abnormalities was 53% after the first EEG and 72% after the third EEG. Among subjects with single unprovoked seizure, the cumulative yield was 39% after the first EEG and 68% after the third EEG. Young age at diagnosis and idiopathic etiology were risk factors for finding epileptiform abnormalities across all EEGs. SIGNIFICANCE: While the cumulative yield of epileptiform abnormalities increases over successive EEGs, there is a decrease in the increment for each additional EEG after the first EEG. This is most evident in incident epilepsy and in younger subjects. Clinically it may be worthwhile to consider that the probability of finding an epileptiform abnormality after the third non-epileptiform EEG is low.